Effect of two types of FRC posts on the root canal wall retention - Arash Zar Bakhsh; Ezzatollah Jalalian; Nilufar Rahimi; Shahrzad Sadr Haghighi (Tehran University of Medical Sciences, 2016)
Background and Aims: The zirconia coated FRC posts (Ice light) is the next generation of aesthetic posts , ice light features 70% fill of zirconia enriched, parallel glass fiber for exceptional strength. Its flexibility is close to dentine so stress is distributed. The aim of this study was to evaluate the effect of post type (FRC post and the zirconia coated FRC post) on the retention to the root canal wall. Materials and Methods: 20 extracted human premolar teeth with 14 mm length were selected. After post space preparation, the teeth were randomly divided into two groups: Group1: the zirconia coated FRC post (Danville, USA) Group2: FRC post (RTD DT light post, France). All posts were cemented with a dual-cure resin cement (Panavia, Kuraray, Japan). All specimens were mount in acrylic cylinders, and the push-out test was done using a universal testing machine (Instron 5500 R, USA) at 1 mm/min speed. Data were analyzed using T-test. Results: The retentive strengths were in coronal (75.27+14.81 MPa), in middle (64.38+15.29 MPa) and in apical (51.46+13.29 MPa) for the zirconia coated FRC post, and also were in Coronal (59.16+1.91 MPa), in middle (66.83+12.32 MPa) and in apical (67.88+17.47 MPa) for the FRC post. There was no significant difference in mean retentive strength between two groups in each region (P=0.07). Conclusion: The FRC post and zirconia coated FRC post had similar retention to the root canal walls.